Faktor-Faktor Mempengaruhi Kepatuhan Pembayaran Pajak (Studi Kasus Pengusaha Restoran di Kabupaten Lumajang) - Murdiansyah, Isnan; Wahyuni, Nanik; Siswanto, Siswanto (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2020)
One of the local taxes that can support regional income is restaurant tax. Restaurant tax is a tax on services provided by restaurants. What is meant by a restaurant is a food and beverage provider facility that is free of charge, which also includes restaurants, cafeterias, canteens, food stalls, bars, and the like, including catering services. Restaurant tax is one of the potential local taxes in the future, because as Lumajang Regency develops, it starts to become a tourism destination city with the discovery of new tourist attractions, such as: B-29, Biting Sites and others, thus causing a large effect which marked the beginning of the growth of new shopping centers and the construction of cafes in the shopping center. This study aims to examine the factors that influence the compliance of tax payments for restaurant entrepreneurs in Lumajang. The results of this study provide empirical evidence that the application of the Tax Law does not have a significant positive effect on compliance with paying restaurant taxes, tax counseling does not have a significant positive effect and tax penalties have a significant positive effect and awareness of taxpayers has a significant negative effect on tax compliance.